Research on smart authentication authorization and accounting in next generation network - ZHANG Hong (Tongxin xuebao)
With the fast development of Internet,there were more and more network access methods and network services.But too many accounts were inconvenient for users to perform the AAA（authentication,authorization and accounting）,and many service providers hadn’t appropriate AAA mechanisms.In order to solve these problems,the smart AAA was introduced.The architecture of the smart AAA was designed,and SOAP based SAML was used to exchange security information between smart AAA and other service providers.Analysis indicates the smart AAA will provide the universal and intelligent AAA services for both users and operators.